Mechanism of Zn(II) enhanced biodegradation of m-dichlorobenzene. Issue 1 (1st January 2021) - Shang, Qingqing; Yang, Bairen; Wu, Menglei; Li, Yue; Wang, Jiajie; Zhang, Hao; Sun, Zhuqiu; Wang, Liping
ABSTRACT: M-dichlorobenzene can be degraded through biotrickling filter (BTF). However, its degradation needs to be enhanced, and the mechanism of enhancement is unclear. In this study, Zn(II) was taken as the biological growth promoter; the polysaccharides and proteins, zeta potential, Fourier transform infrared spectroscopy, x-ray photoelectron spectroscopy, and the enzyme activity of the strains were analyzed. The results indicated that Zn(II) at 5mg/L promoted the growth of the strain. When the inlet concentration was 505.74 mg/m 3 and the empty bed resistance time (EBRT) was 90 s, the removal efficiency of BTF2 was 86.15%. In BTF2, the enzyme activity, polysaccharide, and protein content increased, while the zeta potential decreased. The changes of zeta potential indicated that there existed an electrostatic interaction between extracellular polymeric substance (EPS) and Zn(II). The results of Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy confirmed that there was a bond between the EPS surface functional groups and Zn(II).